Ultrasensitive measurement of brain penetration mechanics and blood vessel rupture with microscale probes - Abdulmalik Obaid; Mina-Elraheb Hanna; Song-Wen Huang; Yu-Ting Hu; Omar Jáidar; William Nix; Jun B. Ding; Nicholas A. Melosh; Yu-Wei Wu (Proceedings of the National Academy of Sciences, 2026)
Microscale electrodes, on the order of 10 to 100 µm, are rapidly becoming critical tools for neuroscience and brain–machine interfaces for their high channel counts and spatial resolution, yet the mechanical details of how probes at this scale insert into brain tissue are largely unknown. Here, we performed quantitative measurements of the force and compression mechanics together with real-time microscopy for in vivo insertion of a systematic series of microelectrode probes as a function of diameter (7.5 to 100 µm and rectangular Neuropixels) and tip geometry (flat, angled, and electrochemically sharpened). These results elucidated the role of tip geometry, surface forces, and mechanical scaling with diameter. Surprisingly, the insertion force postpia penetration was constant with distance and did not depend on tip shape. Real-time microscopy revealed that at small enough lengthscales (<25 µm), blood vessel rupture and bleeding during implantation could be entirely avoided. This appears to occur via vessel displacement, avoiding capture on the probe surface which led to elongation and tearing for larger probes. We propose a three-zone model to account for the probe size dependence of bleeding, and provide mechanistic guidance for probe design.